RETRACTED: Geological structure of Ustuk ore field features of mining - Togaev Isomiddin; Abdujabborov Baxtinur; Toshtemirov Shoxrux (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001